The Protection of the Historic City: The Case of the Surroundings of the Lonja de la Seda in Valencia (Spain), UNESCO World Heritage - Camilla Mileto; Fernando Vegas López-Manzanares (Architecture, 2023)
In geographical terms, historic cities possess an inertia in regard to the modification of urban function. This explains why buildings may change over time, but the location of the functions remains. For over a thousand years, the city of Valencia has concentrated the commercial activity of its historic centre around the building of the Lonja de la Seda, its surrounding buildings, and its adjacent spaces, streets and squares. Recent constructions coexist with centuries-old buildings, witnesses to the transformations of this urban enclave, which has retained its commercial function. Although the Lonja de la Seda was declared World Heritage by UNESCO in 1996, its surroundings, despite being of interest and closely linked to the protected building, were not. This article analyses the history and evolution of the built fabric and urban spaces of this complex, which represents the nerve centre for commerce in the city of Valencia. This text presents research based on studies carried out directly on the buildings in this context by the authors, as well as indirect examinations of documentation from the archives and the existing bibliography. The aim of this study is to showcase how combining material and documentary studies can lead to a broader definition of the tangible and intangible values of cultural heritage. This, in turn, could lead to the comprehensive enhancement of the historic city, where historic residential fabric and notable buildings are merely manifestations of the process for the construction of the city.